Heat exposure and productivity loss among construction workers: a meta-analysis - Shurong Han; Lin Dong; Yulei Weng; Jianjun Xiang (BMC, 2024)
Abstract Background Global warming is raising increasing concerns about its impact on worker productivity, particularly in industries like construction where outdoor physically demanding jobs are prevalent. This study aimed to perform a meta-analysis to assess the existing evidence on the impact of heat exposure on productivity loss among construction workers. Methods We conducted a comprehensive literature search across six databases-Web of Science, PubMed, Embase, Scopus, ScienceDirect, and IEEE-covering the period from database inception to September 18, 2024. The Joanna Briggs Institute (JBI) critical appraisal checklist was used for quality assessment. A random-effect model meta-analysis was performed, and publication bias was evaluated by Egger's and Begg's tests. Results From an initial pool of 1209 studies, 14 met the inclusion criteria, representing data from 2387 workers. Our findings indicate that 60% (95% CI: 0.48-0.72, p < 0.01) of construction workers exposed to elevated temperatures experienced significant productivity loss. Productivity loss was more pronounced when the Wet Bulb Globe Temperature (WBGT) exceeded 28 °C or when ambient temperatures surpassed 35 °C. Furthermore, workers aged over 38 (proportion = 0.61, 95% CI: 0.49-0.72) and teams with female workers (ratio = 0.74, 95% CI: 0.60-0.87) were more susceptible to productivity loss. Conclusions This review highlights heat exposure as a significant factor affecting productivity in the construction industry. We recommend prioritizing the protection of vulnerable groups such as women and older workers, developing innovative technologies and equipment for working in hot conditions, and improving the working environment to safeguard workers' health and productivity. Further research is needed to investigate the long-term health impacts of heat exposure and develop strategies for optimizing microclimate management in construction settings.